The Knowledge and Skill Readiness of TVET Trainee in Construction Program for Green Construction Project Management - Mohamad, Mimi Mohaffyza; Ruslan, Rus Farah Ilyliya; Fatin Najwa Mohd Nusa; Adnan Ahmad (Online Journal for TVET Practitioners, 2023)
Project management with the concept of green building construction requires competence efficiency compared to conventional building project management. The readiness of prospective workers in the construction field also needs to be identified as it is a requirement. This study was conducted to identify the readiness of TVET trainees from two different TVET institutions in managing green concept construction projects. Readiness identified based on critical knowledge and soft critical skills. The study’s objective was to identify the level of critical knowledge and soft critical skills readiness as well as to identify the differences in the readiness of TVET trainees from two different institutions. The study was conducted in a survey using a quantitative approach. The research instrument used was a questionnaire, and the study was conducted in two TVET institutions from different ministries (please stated name of the institutions and ministries. A total of 153 trainees as respondents and a simple random sampling method was used to determine the study sample. The findings show that the level of critical knowledge and soft critical skills are at a high level (both institutions?), and there are differences between these two TVET institutions in terms of critical knowledge, while there is no difference in terms of soft critical skills. Overall, the study shows that the TVET trainees are prepared in knowledge and skills in green concept construction project management. This study can be a part of reference for TVET programs, trainee, and trainers especially in Construction to ensure the aspects of critical knowledge and skills can be improved align with industry need.